FAMILY BOMBYLIIDAE - Lamas, Carlos José Einicker; Evenhuis, Neal L. (Zootaxa, 2016)
Bombyliidae is one of the largest Diptera families with more than 4,500 recognized species worldwide. Their species vary from robust to thin, and may be small to large (2-20mm) and looks like bees or wasps. They also present great variation in color. Adults can often be seen either resting and sunning themselves on trails, rocks or twigs or feeding on flowering plants as they are nectar feeders. All reared bee flies are predators or parasitoids of arthropods. The Colombian fauna of bombyliids comprises at the moment 22 species, and 12 genera, of which, six are endemic species. Nonetheless, this number may be much higher, as Colombia is a megadiverse country and there are not many specimens of this family deposited in collections all over the world.